Effects of medication intake on the risk of hemorrhage in patients with sporadic cerebral cavernous malformations - Chen, Bixia; Lahl, Kirstin; Saban, Dino; Lenkeit, Annika; Rauschenbach, Laurèl; Santos, Alejandro N.; Li, Yan; Schmidt, Boerge; Zhu, Yuan; Jabbarli, Ramazan; Wrede, Karsten H.; Kleinschnitz, Christoph; et al. (Frontiers in Neurology, 2023)
Objective Recurrent intracerebral hemorrhage (ICH) poses a high risk for patients with cerebral cavernous malformations (CCMs). This study aimed to assess the influence of medication intake on hemorrhage risk in sporadic CCMs. Methods From a database of 1,409 consecutive patients with CCM (2003–2021), subjects with sporadic CCMs and complete magnetic resonance imaging data were included. We evaluated the presence of ICH as a mode of presentation, the occurrence of ICH during follow-up, and medication intake, including beta blockers, statins, antithrombotic therapy, and thyroid hormones. The impact of medication intake on ICH at presentation was calculated using univariate and multivariate logistic regression with age and sex adjustment. The longitudinal cumulative 5-year risk for (re-)hemorrhage was analyzed using the Kaplan–Meier curves and the Cox regression analysis. Results A total of 1116 patients with CCM were included. Logistic regression analysis showed a significant correlation (OR: 0.520, 95% CI: 0.284–0.951, p = 0.034) between antithrombotic therapy and ICH as a mode of presentation. Cox regression analysis revealed no significant correlation between medication intake and occurrence of (re-)hemorrhage (hazard ratios: betablockers 1.270 [95% CI: 0.703–2.293], statins 0.543 [95% CI: 0.194–1.526], antithrombotic therapy 0.507 [95% CI: 0.182–1.410], and thyroid hormones 0.834 [95% CI: 0.378–1.839]). Conclusion In this observational study, antithrombotic treatment was associated with the tendency to a lower rate of ICH as a mode of presentation in a large cohort of patients with sporadic CCM. Intake of beta blockers, statins, and thyroid hormones had no effect on hemorrhage as a mode of presentation. During the 5-year follow-up period, none of the drugs affected the further risk of (re-)hemorrhage.